Pinchas Zukerman here to make music - Zukerman, Pinchas 1948-; Nupen, Christopher; Nupen, Christopher; Barenboim, Daniel 1942-; Du Pré, Jacqueline 1945-1987; Beethoven, Ludwig van 1770-1827
Made over a period of seven years from 1967 to 1974 and contains sound recordings which date back to when Pinchas Zukerman was 9 years old. Together with a complete performance of Beethoven's Trio op. 70, no. 1 by Daniel Barenboim, Pinchas Zukerman and Jacqueline du Pré, made in 1970
Title from resource description page (viewed Jul. 25, 2014)
Keywords: Piano trios; Violinists; Violinists -- Israel -- Biography; Zukerman, Pinchas / 1948-; Israel; Streaming videos; Biographies; Documentary films